Image analysis to determinate the saponin content in quinoa - Souza, Luiz Augusto Copati; Spehar, Carlos Roberto; Santos, Roberto Lorena Bastos (Pesquisa Agropecuaria Brasileira, 2004)
A group of washed seeds and thirty five genotypes of quinoa (Chenopodium quinoa, Willd) were screened by soap column method and were classified by RGB Color Model (R, red; G, green; B, blue) with the objective to determine the influence of the saponin content in the grain color. Yellow seeds presented high levels of saponin. There was negative correlation (p≤0.05) among soap column method and bands R (r = -0.751), G (r = -0.660) and B (r = -0.594). Four groups were fixed. Tests confirmed the access of group 4 as bitter (yellow seeds) and the access of group 1 as sweet (white seeds). The dispersion represents probable difference in gene frequency, reflected by the color and rate of saponin.